2020
DOI: 10.26434/chemrxiv.12678404.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stabilization of Supramolecular Membrane Protein-Lipid Bilayer Assemblies Through Immobilization in a Crystalline Exoskeleton

Abstract: <div> <div> <div> <p>Artificial native-like lipid bilayer systems constructed from phospholipids assembling into unilamel- lar liposomes allow the reconstitution of detergent-solubilized transmembrane proteins into supramolecular lipid-protein assemblies called proteoliposomes, which mimic cellular membranes. Stabilization of these com- plexes remains challenging because of their chemical composition, the hydrophobicity and structural instabil- ity of membrane proteins, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This study was interesting because they showed a more stable method to encapsulate antigens and demonstrated that the biomaterial could prime the immune system without the need of the adjuvant. A more recent development has shown that biomimetic coating of ZIFs on lipid nanoformulations promote their stability for many months in the mail (Herbert et al, 2021). This could have potential applications for stabilizing the newest lipid‐based vaccines.…”
Section: Types Of Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was interesting because they showed a more stable method to encapsulate antigens and demonstrated that the biomaterial could prime the immune system without the need of the adjuvant. A more recent development has shown that biomimetic coating of ZIFs on lipid nanoformulations promote their stability for many months in the mail (Herbert et al, 2021). This could have potential applications for stabilizing the newest lipid‐based vaccines.…”
Section: Types Of Biomaterialsmentioning
confidence: 99%
“…This required cooling/cold‐chain makes the delivery of vaccines expensive, and the cost of keeping them cold can account for as much as 80% of the total cost of the immunization (Ashok, Brison, & LeTallec, 2017; Bogataj, Bogataj, & Vodopivec, 2005; Karishma, Donna, Timothy, & Neena, 2012; Setia et al, 2002; Welch et al, 2018). This instability has made controlled release strategies for delivery of LNP‐based vaccines difficult, though emerging approaches using metal–organic frameworks have shown considerable promise (Herbert et al, 2021). The ideal 21st‐century vaccine should be safe, patient‐friendly, and stable enough such that it can be stored at ambient conditions and provide long‐term immunity after one administration.…”
Section: Introductionmentioning
confidence: 99%
“…Biomimetic mineralization with ZIF is extremely gentle and we have previously shown that membrane bound proteins are not only preserved but protected by ZIF encapsulation in lipid nanoparticles. 73 To show that our ZIF encapsulation approach preserves natively folded proteins better than traditional methods of inactivation, we conducted an agglutination assay using yeast. The fimbriae on the surface of CFT073 contain glycoproteins that are highly specific binders of sugar.…”
Section: Uropathogenic E Coli Support Growth Of Zifmentioning
confidence: 99%
“…Biomimetic mineralization with ZIF is extremely gentle and is known to not alter the conformation of membrane bound proteins. 69 We tested whether ZIF encapsulation inactivates CFT073. Following formation of the ZIF shell, immobilized CFT073 was incubated for 30 min at room temperature and exfoliated with 500 mM sodium acetate buffer.…”
Section: Uropathogenic E Coli Support Growth Of Zifmentioning
confidence: 99%
See 1 more Smart Citation